Significado paleoambiental de silicofitólitos em rampa de colúvio e paleocabeceira de drenagem na superfície de Palmas - Água Doce - Paisani, Sani Daniela Lopes (2015)
This study aimed to identify the meaning of the phytholith palaeoenvironmental record in pedostratigraphic sequences of colluvial ramps and paleovalley head on the geomorphic surface Palmas / Água Doce. In particular it sought to: a) distinguish phytholith record incorporated into colluvium by modern vegetation of the areas studied in relation to the registration of paleovegetation area source of colluvium; b) understand the phenomenon of absense of phytholith records on the basis of colluvial deposits; c) characterize the taphonomical morphotypes; d) search current homologous in the first centimeters of soil, regarding the impact of pastoral activity; e) systematize the stratigraphic information from colluvial deposits in the study area, and f) establish the carbon isotopic signal to the sections of phytholith record for mutual comparison of paleovegetation of information obtained by phytholith analysis. To achieve the objectives two pedostratigraphic sections were chosen, a representation of pedostratigraphic sequence of colluvial ramp (HS18) and a paleovalley head (HS13), both in geomorphic surface Palmas / Água Doce. In the colluvium ramp feces from cattles were analyzed, since the pastoral activity is recurrent in the study areas since the late nineteenth century and until now no one knew of its their role as a developer of phytoliths to pedostratigraphic sequences. By integrating the records of phytoliths from both geomorphic units it can be said that: a) phytholith in pedostratigraphic sequences of colluvium ramps and paleovalley head of the geomorphic surface of Palmas/ Água Doce are both autochthonous and allochthonous; where the first represents the occupation of the graaslands vegetation over time along with the surfaces and paleosurfaces; b) the allochthonous also represents the graaslands vegetation, but from the slopes that surround the colluvium ramp and paleovalley head; c) the activity of current and past grazing is a taphonomy process of incorporation of allochthonous morphotypes into the soil and degradation as a result of chewing and digestion; d) the absence of phytoliths with preserved morphologies in both pedostratigrafic units shows the degradation of these corpuscles both naturally and by digestion of herbivorous animals; e) morphotypes are common taphonomy chemically, physically as well as both.